The Effectiveness of the PKH Social Assistance Program in Reducing Extreme Poverty in Kerta Village, Banjarsari District in 2025 - Ariyan, Said; Agustina, Winda (MID Publisher International, 2024)
This study aims to analyze the effectiveness of the Family Hope Program (PKH) in reducing extreme poverty in Kerta Village, Banjarsari District, in 2025. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation of beneficiaries, program facilitators, and Social Service officers. The results of the study show that social assistance programs such as PKH and Direct Cash Assistance (BLT) have a significant positive impact on improving people's welfare, especially in meeting the basic needs of poor households. However, the effectiveness of the program is still hampered by planning problems, inaccurate beneficiary data, and limited coordination between agencies. Efforts to increase the effectiveness of the program can be carried out through the digitization of the data collection system to strengthen the accuracy of poverty data, increase the literacy of beneficiaries regarding the use of assistance, and strengthen cross-agency coordination so that interventions against extreme poverty are more targeted and sustainable. Overall, the implementation of PKH in Kerta Village has shown quite good results, but it still needs continuous evaluation and innovation so that it can become a strategic instrument in accelerating the elimination of extreme poverty in rural areas.